Safety and reliability of complex engineered systems proceedings of the 25th European Safety and Reliability Conference, ESREL 2015, Zürich, Switzerland, 7-10 September 2015 - Podofillini, Luca; Sudret, Bruno; Stojadinović, Božidar; Zio, Enrico; Kröger, Wolfgang 1945- (CRC Press, 2015)
The main goal of this book is to showcase the advancements in understanding, modeling and management of complex engineered systems. The book offers a multidisciplinary platform to address technological, societal and financial aspects of system safety and reliability. Emphasis is given to the intra- and interdependencies of functions and the cascading failures that characterize complex engineered systems.